Parafunctional habits and botulinum toxin: A narrative review of the literature (Research, Society and Development, 2023)
Parafunctional habits, such as bruxism, involve abnormal muscular and dental activities that can cause serious orofacial dysfunction, including tooth wear, fractures, temporomandibular joint pain and sleep disorders. Orofacial harmonization, which combines aesthetic and functional procedures to improve the aesthetics and function of the orofacial region, plays a crucial role in minimizing the harmful effects of bruxism. This involves the use of customized bite plates, application of botulinum toxin to relax the chewing muscles and aesthetic and functional rehabilitation of damaged teeth. Botulinum toxin, known for its applications in aesthetic and neurological medicine, has stood out as an effective supporting option in the treatment of bruxism. Acting by inhibiting the release of acetylcholine in neuromuscular junctions, it reduces the strength of muscle contractions during episodes of bruxism, relieving pressure on the teeth and temporomandibular joint. The approach is non-invasive and temporary, offering an attractive alternative to traditional techniques. However, its application must be carried out by qualified healthcare professionals to ensure safe and effective results. Therefore, botulinum toxin emerges as a promising supporting option in the management of bruxism, contributing to improving the quality of life of patients affected by these parafunctional habits. Thus, this narrative literature review research aims to demonstrate scientific literary production on the possibility of applying supporting therapies, such as botulinum toxin, in the management of parafunctional habits, such as bruxism.